Relationship between Furocoumarin Intake and Melanoma History among US Adults in the National Health and Nutrition Examination Survey 2003-2012. (2nd January 2020) - Melough, Melissa M.; Kim, Kijoon; Cho, Eunyoung; Chun, Ock K.
Abstract: Furocoumarins are a group of phototoxic compounds found in numerous edible plants. Data from cohort studies have suggested that consumption of certain furocoumarin-rich foods may increase skin cancer risk. However, no study has specifically tested this hypothesis by estimating furocoumarin intake and assessing its relationship with skin cancer. This study aimed to estimate average daily furocoumarin intake of US adults using the National Health and Nutrition Examination Survey (NHANES) 2003-2012 and to examine the relationship between furocoumarin intake and melanoma history. A database of the contents of seven furocoumarins in 29 popular foods was linked to dietary data in NHANES 2003-2012. Mean total intake of the selected furocoumarins among US adults was 81.4 μg/day (standard error = 5.5). A total of 75 participants reported a history of melanoma. Using non- and low consumers (<50th percentile) as a reference, and after adjusting for potential confounders, OR (with 95% confidence interval) of melanoma history for the top 10 percent, 80–90th percentiles, and 50–80th percentiles were 1.75 (0.43–7.20), 1.66 (0.39–7.16), and 0.90 (0.45–1.78), respectively. Furocoumarins are widely consumed among US adults, and a trend towards higher odds of melanoma history was observed among those with higher furocoumarin intake, although this relationship was not statistically significant.